THE EFFECT OF DELEGATIVE LEADERSHIP STYLE AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE ON CV WIRASANDI - Sanjaya, Rizky Dwi; Pratami, Lefi Agastasia; Muldani, Dwi Mentari Sukma; Rizky, Muhamad; Permata, Putri Millennia; Rahmayanti, Rima; Roespinoedji, Djoko (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine the effect of delegative leadership style variables and non-physical work environment variables on employee performance on CV Wirasandi, Cimahi This type of research is quantitative research. The sample in this study amounted to 102 employees. Collecting data by using non-probability sampling technique and the analysis method in this study is multiple regression analysis. Furthermore, the technical data processing using Statistical Package for Social Science (SPSS) version 25 software. The results of this study indicate that the delegative leadership style and non-physical work environment have a positive effect on employee performance. Delegative leadership style has no significant effect on employee performance. The non-physical work environment has a significant effect on employee performance.